Mucin 5AC expression is common but unrelated to tumor progression in pancreatic adenocarcinoma. (31st May 2022) - Dwertmann Rico, Sebastian; Büscheck, Franziska; Dum, David; Luebke, Andreas M; Kluth, Martina; Hube-Magg, Claudia; Hinsch, Andrea; Höflmayer, Doris; Perez, Daniel; Izbicki, Jakob R; Neipp, Michael; Mofid, Hamid; et al.
Introduction: Mucin 5AC (MUC5AC) belongs to the family of secreted gel-forming mucins. It is physiologically expressed in some normal mucin producing epithelial cells but also in pancreatic, ovarian, and colon cancer cells. The role of MUC5AC expression in cancer is not fully understood. This study was designed to explore the role of MUC5AC for pancreatic cancer progression, its association to microsatellite instability, and its diagnostic utility.Methods: Mucin 5AC expression was studied immunohistochemically in a tissue microarray (TMA) from 532 pancreatic cancers, 61 cancers of the ampulla Vateri, six acinar cell carcinomas and 12 large sections of pancreatitis.Results: Mucin 5AC staining was interpretable in 476 of 599 (79%) arrayed cancers. Staining was completely absent in normal pancreas and pancreatitis, but frequent in pancreatic cancer. Membranous and cytoplasmic MUC5AC expression was most common in pancreatic adenocarcinomas (71% of 423), followed by carcinomas of the ampulla Vateri (43% of 47), and absent in six acinar cell carcinomas. Mucin 5AC expression was unrelated to tumor phenotype (tumor stage, tumor grade, lymph node, and distant metastasis), and microsatellite instability in ductal adenocarcinomas and carcinomas of the ampulla Vateri.Conclusion: Our study indicates that MUC5AC is an excellent biomarker for pancreatic cancer diagnosis, especially to support the sometimes-difficult diagnosis on small biopsies. Mucin 5AC expression is unrelated to pancreatic cancer aggressiveness.